Yield and quality of cool-season perennial grasses for forage and biomass feedstocks in Northeast Colorado - Gillette, Katrina Lynn, author; Hansen, Neil C., advisor; Brummer, Joe E., committee member; Qian, Yaling, committee member (Colorado State University. Libraries, 2011)
The burning of fossil fuels has led to an increase of the greenhouse gas CO2, which traps heat and increases temperatures of the global climate. The increases of the greenhouse gases, CO2, CH4 and N2O, have been attributed as the cause of the climatic warming during the industrial era. One identified GHG mitigation strategy is the use of long term perennial grass production for bio-fuel use and rangeland restoration. It is estimated that biofuels could offset 30% of current fossil fuel use. Switchgrass, a C4 grass species, was chosen by the DOE as the model crop for cellulosic biofuel because of the plant's perennial nature, high water use efficiency, wide range of exploitable genetics, and its ability to be grown in diverse regions. Yield potentials are often lower for cool-season grasses, but for warm-season grasses like switchgrass difficult establishment and winter stand loss from extreme conditions can be a problem for production. There are many C3 species utilized in the Northeastern and the Western of the United States for rangeland and pasture cattle production. Production difficulties are less likely in some of the hardier C3 grasses in cooler environments. C3 grasses have been historically utilized for animal forage because of superior digestibility and high feed values. The high digestibility is directly correlated to reduced lignin content. Lignin is a primary barrier to the bioconversion process to make ethanol. Increasing the polysaccharide to lignin ratio is one identified route to increasing bio-fuel feedstock quality. These qualities produced in C3 grasses could create a dual feedstock for both animal and bio-fuel production. This may even decrease competition for land resources between livestock producers and bio-energy crop production. Relying on a diversity of bio-energy crops in ecologically different regions will allow for greater stability, resistance, and resilience to climatic and environmental variability. The goals of this study are to compare forage quality analyses of C3 grasses, seasonal partitioning of dry matter (DM), crude protein content (CP), and neutral detergent fiber (NDF) and acid detergent fiber (ADF). Fifteen cool-season grasses were selected based on potential productivity under limited irrigation typical to Eastern Colorado. Two spring harvest dates were selected based on important production phases of the plant. The June 1, 2009 harvest (H1) corresponded to the boot to early heading stage. The average for the species statistically grouped the highest yield was 4500 kg/ha. The second spring harvest (H2) was on June 22, 2009 and corresponded to the mid to late heading stage and average yields for this harvest was 6390 kg/ha. These are high yields for the Eastern Plains of Colorado, but it is important to point out at that 2009 had an exceptionally wet spring and summer for the region. Tall, intermediate, crested and western wheatgrass were species that performed the best for the delayed harvest in terms of biofuels quality because they had the greatest increases in yield and structural carbohydrates, measured in NDF and ADF analysis. These species also had the greatest decrease in CP content. However, in general all species retained fairly high CP levels of over 10%, which is too high for biofuel quality standards, and an even further delay in harvest timing is recommended to decrease CP levels. This may be easily attained since forages evaluated decreased in quality at a rapid rate after seed head emergence. There are two major hurdles for the use of these forages as biofuels: 1) competition from feedstock and livestock feeders and 2) reducing the CP levels of the forages.
Keywords: biofuels; forage quality; cool-season grasses; climate change